Limitations in Simulation of Building Pounding in Earthquakes. Issue 2 (June 2014) - Khatiwada, Sushil; Chouw, Nawawi
Several methods have been proposed for the analysis of building pounding. In previous studies some of these models have been considered in isolation, while others have been studied as a specific configuration of buildings. Although the pounding force predicted by each model varies significantly, results from the evaluation of these models have been inconclusive. This leads to uncertainties in the practical applications of pounding force models. This study addresses the limitations in numerical and experimental simulations of building pounding. The Sears impact model is suggested to overcome some of these limitations. It is concluded that contact stiffness and coefficient of restitution are the main reason for the diverse numerical results, while differences observed in the experiments could be due to sampling rate and instrumental constraints.